Intrafamilial, Preferentially Mother‐to‐Child and Intraspousal, Helicobacter pylori Infection in Japan Determined by Mutilocus Sequence Typing and Random Amplified Polymorphic DNA Fingerprinting. Issue 5 (9th February 2015) - Yokota, Shin‐ichi; Konno, Mutsuko; Fujiwara, Shin‐ichi; Toita, Nariaki; Takahashi, Michiko; Yamamoto, Soh; Ogasawara, Noriko; Shiraishi, Tsukasa
Abstract: Background: The infection route of Helicobacter pylori has been recognized to be mainly intrafamilial, preferentially mother‐to‐child, especially in developed countries. To determine the transmission route, we examined whether multilocus sequence typing (MLST) was useful for analysis of intrafamilial infection. The possibility of intraspousal infection was also evaluated. Materials and Methods: Clonal relationships between strains derived from 35 index Japanese pediatric patients, and their family members were analyzed by two genetic typing procedures, MLST and random amplified polymorphic DNA (RAPD) fingerprinting. Results: Mostly coincident results were obtained by MLST and RAPD. By MLST, the allele of loci in the isolates mostly matched between the index child and both the father and mother for 9 (25.7%) of the 35 patients, between the index child and the mother for 25 (60.0%) of the 35 patients. Conclusions: MLST is useful for analyzing the infection route of H. pylori as a highly reproducible method. Intrafamilial, especially mother‐to‐children and sibling, infection is the dominant transmission route. Intraspousal infection is also thought to occur in about a quarter in the Japanese families.